Perencanaan Pariwisata Berbasis Karakteristik Wilayah Pedesaan (Studi Sosiologi Pariwisata Di Desa Dulumai Kecamatan Pamona Puselemba Kabupaten Poso) - Yakin Ngguna; Sofian Melangi Ulungi; Adriani Galry Adoniram Tobondo (Interdisciplinary Journal (IDe), 2023)
This study aims to analyse and conduct a tourism planning model based on the characteristics of rural areas. The location of this study is in Dulumai village, Pamona Puselemba District, Poso Regency. The research method used is descriptive qualitative. Based on a series of studies, the results were obtained that the planning for the development of Dulumai village as a tourist destination area can be carried out by involving all elements of the community in every decision making through village deliberations. The Village Government needs to carry out guidance and empowerment of the community in an effort to manage the potentials in Dulumai. The community needs to re-preserve local wisdom that no longer exists. In order for Dulumai to become a tourist destination, the local government needs to do several things, namely it is necessary to involve the entire community in every decision or policy making in every Village deliberation. It is also necessary to empower and nurture the community in order to be able to process their potentials. The local wisdom that once existed needs to be preserved and maintained what still exists today.